2017
DOI: 10.1063/1.4975660
|View full text |Cite
|
Sign up to set email alerts
|

Phase-locking of multiple magnetic droplets by a microwave magnetic field

Abstract: Manipulating dissipative magnetic droplet is of great interest for both the fundamental and technological reasons due to its potential applications in the high frequency spin-torque nano-oscillators. In this paper, a magnetic droplet pair localized in two identical or non-identical nano-contacts in a magnetic thin film with perpendicular anisotropy can phase-lock into a single resonance state by using an oscillating microwave magnetic field. This resonance state is a little away from the intrinsic precession f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…We consider that the magnetic dipolar (magnetostatic) interactions affecting the magnetic dynamics of the droplet pair mainly originates from the spins at the part-II region. 26 The dipolar interactions can therefore be calculated by integrating the transient magnetostatic energy due to the magnetic charges generated by the in-plane magnetization. 27 It can be further simplified as: 28 E…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…We consider that the magnetic dipolar (magnetostatic) interactions affecting the magnetic dynamics of the droplet pair mainly originates from the spins at the part-II region. 26 The dipolar interactions can therefore be calculated by integrating the transient magnetostatic energy due to the magnetic charges generated by the in-plane magnetization. 27 It can be further simplified as: 28 E…”
Section: -mentioning
confidence: 99%
“…One approach to solving this problem can be done by using phase-locking technique through a microwave oscillating magnetic field to synchronize the multiple droplets. 26 However, another study reported that droplets cannot be locked to an external microwave ac current signal. 29 On the other hand, merging multiple droplets into a large droplet may also enhance the output signal because the precession region (part-II) is enlarged.…”
Section: B Merging the Droplet Pairmentioning
confidence: 99%
“…Due to nonlinearities in the magnetic system, an intrinsic connection of the frequency to the oscillation amplitude occurs [13]. This allows to tune SHOs directly by the strength of the driving spin current and additionally provides an exceptional wide-ranged synchronization to external signals by frequency entrainment [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…After the first experimental demonstration of magnetic droplets, reported in STNOs with a PMA Co/Ni free layer and a Co fixed layer 3 , interest in magnetic droplets continues to increase due to its interesting characteristics, such as a highly nonlinear dynamics 2,11,19 , large power emission 3,10,20,21 , and possible applications in microwave-assisted magnetic recording (MAMR) 22,23 and neuromorphic chips as nonlinear oscillators [24][25][26] . Several theoretical 5,11,15,19,[27][28][29][30][31][32][33] and experimental 6-10, 12, 16, 21, 34-38 studies on magnetic droplets have since been presented. and they identify a possible zero-frequency droplet with a topologically trivial magnetic bubble [39][40][41][42][43] .…”
mentioning
confidence: 99%